Impact of health educational intervention to increase osteoporosis knowledge among women: a systematic review - Amin, Samia; Abdul Rahman, Hejar; Ismail, Suriani; Zainal Abidin, Emilia (Finlogy Publication, 2017)
Osteoporosis is a growing global health concern. It is a silent and incurable disease, and many people are not aware of it till complications occur. Osteoporosis is difficult to treat and still incurable, and so prevention is critically necessary. Indeed, it is preventable by modifying unhealthy lifestyles to maximize bone mass density before its occurrence. Health educational osteoporosis program are known as an important strategy in its prevention. Theses program will increase women’s knowledge levels and alter their health beliefs regarding osteoporosis and preventive behaviors. This paper reports an analysis of the results on osteoporosis educational program for women in different age group.